The Trypanosoma brucei CCCH zinc finger proteins ZC3H12 and ZC3H13 - Benard Aswani, Ouna; Helbig, Claudia; Clayton, Christine (Molecular and biochemical parasitology, 2012)
CCCH-type zinc finger proteins have various roles in RNA metabolism. We here analysed the functional relevance of two such proteins from Trypanosoma brucei, TbZC3H12 and TbZC3H13. Each protein has a single CCCH motif very similar to those seen in metazoan proteins that regulate mRNA degradation. TbZC3H12 is expressed in bloodstream form parasites at low levels. It is phosphorylated, cytosolic and not required for normal growth of cultured bloodstream trypanosomes. RNA interference targeting TbZC3H13, on a TbZC3H12 null background, also had no effect on bloodstream trypanosome growth, but over-expression of tagged TbZC3H13 inhibited procyclic trypanosome growth. Tandem affinity purification of both proteins revealed various interesting potential interactions; specificity was assessed against a list of proteins that were found in 24 other pull-down experiments, which is provided. The conservation of TbZC3H12 in all kinetoplastids, and TbZC3H13 in Salivaria, suggests that the two proteins may be required for optimal growth at some stage of the parasite life-cycle.